Answer:
-16
Step-by-step explanation:
x = -3 is less than -2, so you should use the first equation 5x-1
thus, 5(-3)-1 = -16
5x - 14y = 22 ⇒ 5x - 14y = 22
-6x + 7y = 3 ⇒ <u>12x - 14y = -6</u>
<u>-7x</u> = <u>28</u>
-7 -7
x = -4
5x - 14y = 22
5(-4) - 14y = 22
-20 - 14y = 22
<u>+ 20 + 20</u>
<u>-14y</u> = <u>42</u>
-14 -14
y = -3
(x, y) = (-4, -3)
Answer:
so umm how do u do this
Step-by-step explanation:
Answer:
The percentage decrease = 0.9%
Step-by-step explanation:
Using the formula
Percentage Decrease = [ (Initial Value - Final Value) / |Initial Value| ] × 100
= [(9.80 - 9.71 ) / (9.80)] × 100
= [0.09 / 9.80] × 100
= 0.009 × 100
= 0.9%
Therefore, the percentage decrease = 0.9%